Membangun Kepercayaan dan Memahami Etika Profesional Auditor (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
Related to ethical audits in the present. This research uses literature methods from various articles and books that have been done before. The goal is to find out how a good auditor behaves and still carries out audit ethics professionally. In this preparation using research methods with a literature approach to explore a deep understanding of auditing ethics. The writing of this article focuses on audit ethics that apply Accounting Standards to achieve better audit quality and is based on audit professional ethics. The literature review provides understandingthat a good understanding of audit professional ethics is very important in effective and accountable audit practice.The ethical principles of the audit profession, such as independence, objectivity, integrity, and confidentiality, provide an important framework for auditors in carrying out their work. Through a deep understanding of audit ethics, auditors can carry out their responsibilities with integrity and objectivity, and maintain trust in the public audit profession. In this regard, literature review is a valuable tool in gaining comprehensive insight into professional ethics auditing, as well as building a solid foundation for ethical and dignified auditing practices.